p+(-3)=6.2

Simple and best practice solution for p+(-3)=6.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p+(-3)=6.2 equation:


Simplifying
p + (-3) = 6.2
p + -3 = 6.2

Reorder the terms:
-3 + p = 6.2

Solving
-3 + p = 6.2

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + p = 6.2 + 3

Combine like terms: -3 + 3 = 0
0 + p = 6.2 + 3
p = 6.2 + 3

Combine like terms: 6.2 + 3 = 9.2
p = 9.2

Simplifying
p = 9.2

See similar equations:

| 4(1.5)-6= | | X/-4=2 | | -2(1.5)= | | k-(-4)=2 | | 2/5x-6=8/5x | | 23585x=100000 | | 5y-12x=-41 | | -6(2x+6)=-12+9 | | -2(x+4)+3x= | | 3/8=z-1/8 | | 6(2x-3)+3x=5(2x+6)+30 | | 10/11g-14.8=25.2 | | 3r-7-5r=19 | | -6p-4=-3p+2 | | 1.5+15=2.25r | | 18(v+4)-2v=4(4v+1)-10 | | (3x-29)=(2x+24) | | 7x+11=2x+6 | | 23/5=x/80 | | 4(u-5)-8u= | | Cy=ax+b | | -6p-4=-3+2 | | 3(n+5)-6=#n+9 | | 9x+11x+2=0 | | 2(2-3y)+6y=5 | | -3x+9=-3x+3 | | (12+x)2=8 | | -3s=2 | | y-(-5)=(6/7)(x-3) | | -132=6(-3n+2) | | 6-9p+4p= | | -3(x-8)-5=9(x+2)11 |

Equations solver categories